Investigations of molybdenum-promoted manganese-based solid sorbents for H2S capture. (December 2020) - Ma, Jianyu; Rout, Kumar R.; Sauer, Maximilian; Mahmoodinia, Mehdi; Blekkan, Edd A.
Abstract: The promotion effect of Mo-addition to alumina-supported Mn-based sorbents for high-temperature desulphurization was explored. A series of Mn-based sorbents with fixed Mn-loading and different Mo-loadings were prepared by the wet impregnation method and both fresh and used sorbents were characterized with respect to their physical and chemical properties. The sorbents were active for H2 S removal at 600 °C and could be regenerated by oxidation in diluted air. The sorbents were subjected to 10 repeated sorption/regeneration cycles, and some loss of capacity occurred during the cycles. The results show that Mo-addition promotes the Mn-based sulfur sorbent performance both in terms of capacity and stability. Over the range investigated (0–8 wt% Mo added to a 15 wt% Mn sorbent), the improvement increased with an increasing amount of Mo added. The sample with the highest Mo-addition (15Mn8Mo) also retained the capacity best, as over 90% of the capacity remained after 10 sorption-regeneration cycles, in spite of suffering the most from sintering (observed as loss in surface area, increased pore size, and growth in Mn particle size). Characterization of the fresh and used samples using XRD and Raman spectroscopy indicates that a mixed Mn–Mo oxide suggested to be MnMoO4 plays a role in the promotion mechanism. The sorbent, 15Mn8Mo, is suggested to be promising for high-temperature desulphurization of bio-syngas. Highlights: High-temperature desulphurization using solid sorbents represents an interesting alternative to low-temperature processes. Mn-based sorbent is promising due to thermal stability and sorption kinetics. Mo addition improves the performance of the Mn-based sorbent. The best sorbent investigated, 15Mn8Mo, showed good capacity and stability over repeated sorption and regeneration cycles. Mo-addition leads to the formation of MnMoO4 which is plays a role in the sulfur capture process.